Factors affecting stock returns of firms listed on the Singapore Stock Exchange - Aw, Melissa Xiao Fang (2008)
To examine cross-sectional relationships between average and long run returns of a firm and its size coupled with its book-to-market equity ratio. Our analysis included all firms continually listed on the SGX Mainboard and SESDAQ and conducted for the five-period from June 1998 to June 2003.